Patient Satisfaction With Maternity Waiting Homes in Liberia: A Case Study During the Ebola Outbreak. (4th April 2017) - Lori, Jody R.; Munro‐Kramer, Michelle L.; Shifman, Jordan; Amarah, Patricia N. M.; Williams, Garfee
Abstract : Introduction: Liberia in West Africa has one of the highest maternal mortality ratios in the world (990/100, 000 live births). Many women in Liberia live in rural, remote villages with little access to safe maternity services. The World Health Organization has identified maternity waiting homes (MWHs) as one strategy to minimize the barrier of distance in accessing a skilled birth attendant. However, limited data exist on satisfaction with MWHs or maternal health care in Liberia. Methods: This mixed‐methods case study examines women's satisfaction with their stay at a MWH and compares utilization rates before and during the Ebola outbreak. From 2012 to 2014, 650 women who stayed at one of 6 MWHs in rural Liberia during the perinatal or postnatal period were surveyed. Additionally, 60 semi‐structured interviews were conducted with traditional providers, skilled birth attendants, and women utilizing the MWHs. Quantitative analyses assessed satisfaction rates before and during the Ebola outbreak. Content analysis of semi‐structured interviews supplemented the quantitative data and provided a lens into the elements of satisfaction with the MWHs. Results: The majority of women who utilized the MWHs stated they would suggest the MWH to a friend or relative who was pregnant (99.5%), and nearly all would utilize the home again (98.8%). Although satisfaction with the MWHs significantly decreased during the Ebola outbreak ( P < .001), participants were satisfied overall with the MWHs. Content analysis identified areas of satisfaction that encompassed the themes of restful and supportive environment as well as areas for improvement such as lacking necessary resources and loneliness. Discussion: This case study demonstrated that women using MWHs in Bong County, Liberia are generally satisfied with their experience and plan to use an MWH again during future pregnancies to access a skilled birth attendant for birth. Women are also willing to encourage family and friends to use MWHs.